(untitled) (Andamios, Revista de Investigación Social, 2012)
This article examines, from the urban studies’ perspective, a new human right that has become a social and political demand of growing interest in many cities of the world. This new right means, basically, that cities are for people and not for private business. The article discusses if it is possible to implement this right in the neoliberal era, as well as the challenges of its implementation in a mega city as Mexico City. The left-oriented government of Mexico City has recognized this right in the field of “political commitments”, but simultaneously implements an urban management that promotes private businesses and contributes with them to intensify the socio-spatial inequalities.